If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(x+1/3)*(x-(3/2)) = 0
(x+1/3)*(x-3/2) = 0
( x+1/3 )
x+1/3 = 0 // - 1/3
x = -1/3
( x-3/2 )
x-3/2 = 0 // + 3/2
x = 3/2
x in { -1/3, 3/2 }
| x+(1/6)=2/3 | | -122-5x=3 | | y-(-2)=23 | | -25=-6(5d-2) | | 36=x(x+9) | | +2+5=+19 | | x/2/3=6 | | 6x^3/3x+12 | | 11-k/8=6 | | 3x+8=23-3x | | 6x+4+x=2+2-18 | | -75x=0 | | X+2-2(x-4)=0 | | x/-7=8.1 | | 7g(3g+5x)= | | x^2+y^2-18x+10y+70=0 | | y^2=-6 | | 1.07x=44.94 | | 3x^2+10x-12=-4 | | x^2-8x=6 | | 1/(x^2)=14 | | 6x^3+9x^2+-5x+2=0 | | 8/9x-1=4/5x | | (-1/400)*x^2+1100 | | 3(3r+4)=-33 | | 6x^3+9x^2-5x+2=0 | | 5x+7y=7 | | x+12=5x-2 | | 15x+2y=2 | | x-2*(77-x)-8=0 | | x^2+12x+11x=0 | | 6x^3+9x^2-5x=-2 |